The role of village apparatus in accountability, transparency and responsibility of dana desa management in maguan village - Susilo Aji; Rezza Vitriya; Nur Mufarokhah; Uswatun Khasanah (Trigin Publisher, 2023)
The purpose of this study is to determine the understanding and implementation of the principles of accountability, transparency and responsibility in village fund management. This research uses qualitative discriptive research method. The data collection techniques used are observation, interviews and documentation. The results of the research that the management of village funds in Maguan Village, Ngajum District, Malang Regency in the principles of transparency, accountability and responsibility are quite good, although there are still some obstacles in the implementation in the field that must adjust applicable regulations and the use of responsibilities that can be maximized, it is hoped that the use of the existing web can be maximized so that information can be easily accessed by the people of Maguan Village